The Role of Intergenerational Relationships in Children's Experiences of Community. (7th June 2017) - Bessell, Sharon
Abstract : Community‐strengthening initiatives for children and their families often focus on the provision of services and the development of adult relationships to support children. Less attention is paid to the relationships that children experience within their communities. Drawing on research with over 100 children aged between 8 and 12 years, this paper examines the importance children place on relationships within their communities. More specifically, it explores what children told us about the nature and value of extra‐familial intergenerational relationships.